The INfectious DIsease REgistry BIObank (INDI-REBIO): protocol for the design and implementation of a single-centre, prospective registry and biobank in a tertiary care centre in Italy for advancing infectious disease research - Maurilio Ponzoni; Carmen García; Diana Canetti; Antonella Castagna; Marco Ripa; Paolo Scarpellini; Massimo Locatelli; Simona Bossolasco; Paola Cinque; Angelo Roberto Raccagni; Elena Bruzzesi; Nicola Gianotti; et al. (BMJ Open)
Introduction Infectious diseases are a major global health concern, responsible for significant morbidity and mortality. To advance the understanding and treatment of these diseases, biobanks and biorepositories play a crucial role in guaranteeing sample traceability through their entire life cycle (collection, acquisition and registration, processing, storage, distribution) and future analysis of clinical and biological data.Methods and analysis The INfectious DIsease REgistry BIObank (INDI-REBIO) is an observational, prospective, monocentric, open-ended registry with ad hoc procedures and a systematic collection of uniform clinical, laboratory, imaging and therapeutic data of patients with suspected or microbiologically documented bacterial, viral, fungal and parasitic infectious diseases from the IRCCS San Raffaele Hospital (Milan, Italy). The study aims to collect both uniform data and biological samples such as blood and other relevant specimens. The registry aims to include significant patient numbers across various conditions (among others: bloodstream infections, endovascular infections as infective endocarditis, central nervous system infections, bone and joint infections, multidrug-resistant organisms (MDROs) colonisation, sexually transmitted infections, HIV infection, emerging and re-emerging infectious diseases), enabling comprehensive research on disease evolution, treatment outcomes and the identification of biomarkers.Ethics and dissemination The study adheres to ethical principles outlined by the Helsinki Declaration and Good Clinical Practice guidelines. It has received ethical approval (Comitato Etico CET Lombardia 1, CET 138–2023) and is registered on clinicaltrials.gov (NCT06418048). Participants will provide informed consent and can withdraw at any time. The study results will be disseminated through major international conferences and submitted to peer-reviewed research journals.Trial registration number ClinicalTrials.gov, NCT06418048.